Use of Puzzle Media for Early Childhood: Bibliometric Analysis - sisil, Juleha (UIN Raden Mas Said Surakarta, 2023)
This research aims to become literature related to learning media for early childhood, one of which is puzzles. Knowing the main information from the data obtained. Find out the most journal publications. Find out information related to the origin of the author's education, the most authors, the most countries that publish journals related to puzzle media for early childhood. Displays classification analysis and theme maps related to early childhood puzzle media. Using the help of r studio to find bibliometric data. The type of data obtained comes from Scopus data. The results of puzzle media research have increased from 2016 to 2023. There are 45 countries that have produced articles, namely the USA. The names of the authors who have written 125 articles are unknown. Early Childhood Education is the source of 129 journals. ESCHM is the most affiliation with 14 articles published there.